Concept and strategies of bone tissue engineering - Đorđević Ljubiša B. (Glasnik Antropološkog Društva Srbije, 2016)
In contemporary clinical practice bone substitutes such as implants are used in reconstructive orthopedics and maxillofacial surgery. Judging from physical and chemical properties each implant has some advantages and disadvantages. The idea of bone tissue engineering is to simulate the formation of bone to implants as carriers in combination with osteogenic cells and osteo-stimulative factors (osteoinduction). The design of the implant itself in terms of the chosen carrier with its own characteristics, the type of cells that have been implanted, the type and combination of stimulative factors play an important role in the behavior of the implanted material within a body. Tissue engineering looks promising, however a lot of obstacles have to be surmounted in order to consider it a proper alternative.